Biocompatibility of an experimental MTA sealer implanted in the rat subcutaneous: Quantitative and immunohistochemical evaluation - Viola, Naiana Viana [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP]; da Silva, Guilherme Ferreira [UNESP]; Cerri, Estela Sasso [UNESP]; Tanomaru-Filho, Mario [UNESP]; Cerri, Paulo Sérgio [UNESP] (Wiley-Blackwell, 2012)
The tissue reaction promoted by an experimental mineral trioxide aggregate sealer (MTAS) in the rat subcutaneous was evaluated by morphological and morphometric analyses. In the animals from each group (n = 20), polyethylene tubes filled with MTAS, Portland cement (PC) or MTA were implanted in the dorsal subcutaneous. In the control group, empty tubes were implanted. After 7, 14, 30, and 60 days, the specimens were fixed and embedded in paraffin. In the HE-stained sections, the numerical density of inflammatory cells (IC) in the capsule was evaluated and statistical analyses performed (p = 0.05). The expression of osteopontin (OPN) was evaluated by immunohistochemistry. The von Kossa method for detection of calcified structures was also performed. A moderate inflammatory process in the capsule was seen in all groups, at 7 and 14 days. At 60 days, significant reduction in the number of IC was verified in comparison to initial periods; however, significant differences were not verified among the groups. OPN immunolabeling was observed in the fibroblasts cytoplasm of the capsule next to the implants. Structures von Kossa-positive were observed in the capsule adjacent to all materials implanted at 7, 14, and 30 days. The results strongly indicate that MTAS presents biocompatibility similarly to MTA and PC. (C) 2012 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 2012.
Keywords: biocompatibility; mineral trioxide aggregate; Portland cement; root canal sealer; immunohistochemistry